The Philosophy Of Tri Kaya Parisudha Towards Auditor Pressure Phenomenon Of Audit Procedure Stopping - Ni Putu Riski MARTINI; I Ketut Puja Wirya SANJAYA (Indonesia Strategic Sustainability, 2021)
These cases of audit irregularities indicate a decrease in audit quality, which is caused by a dysfunctional audit behavior. This study discusses the factors that are thought to have an effect on premature termination of audit procedures, which can be caused by external factors related to situational factors during the audit process that will affect the behavior of auditors in conducting audits, namely time pressure and compliance pressure. In addition, the auditors' awareness and sensitivity in preventing or detecting fraud is influenced by the application of a noble local culture, which in Bali is known as the Tri Kaya Parisudha cultural concept. This research was conducted at a public accounting firm in Bali. The research time is 2021. The population of this research is 16 public accounting firms in Bali with 122 auditors. The sampling technique used in this research is purposive sampling technique. Based on the results of the analysis, it can be concluded that: time pressure and compliance pressure have a positive effect on premature audit procedures and the Tri Hita Karana philosophy is able to moderate the relationship between time pressure and adherence pressure on premature audit procedures.